A review on dark fermentative biohydrogen production from organic biomass: Process parameters and use of by-products. (15th April 2015) - Ghimire, Anish; Frunzo, Luigi; Pirozzi, Francesco; Trably, Eric; Escudie, Renaud; Lens, Piet N.L.; Esposito, Giovanni
Highlights: H2 production via dark fermentation of waste biomass is promising. Parameters influencing dark fermentation can be optimized for higher H2 yields. Effluents can be utilized further for energy recovery and for other valued uses. Net energy gain and pH control are important issues. Abstract: Dark fermentation of organic biomass, i.e. agricultural residues, agro-industrial wastes and organic municipal waste is a promising technology for producing renewable biohydrogen. In spite of its potential, this technology needs further research and development to improve the biohydrogen yield by optimizing substrate utilization, microbial community enrichment and bioreactor operational parameters such as pH, temperature and H2 partial pressure. On the other hand, the technical and economic viability of the processes need to be enhanced by the use of valuable by-products from dark fermentation, which mostly includes volatile fatty acids. This paper reviews a range of different organic biomasses and their biohydrogen potential from laboratory to pilot-scale systems. A review of the advances in H2 yield and production rates through different seed inocula enrichment methods, bioreactor design modifications and operational conditions optimization inside the dark fermentation bioreactor is presented. The prospects of valorizing the co-produced volatile fatty acids in photofermentation and bioelectrochemical systems for further H2 production, methane generation and other useful applications have been highlighted. A brief review on the simulation and modeling of the dark fermentation processes and their energy balance has been provided. Future prospects of solid state dark fermentation are discussed.